Reliability Analysis of Emergency Message Broadcast at an Intersection in 2-D VANET - Enzhan Zhang; Yujun Kuang (Dianxin kexue, 2014)
Reliability is an important issue for emergency message broadcast services in vehicular Ad Hoc network （VANET）. Most investigations of such broadcast in VANET focus on multi-hop connectivity, taking all one-hop links for granted. But potential emergency applications of broadcast in VANET include collision avoidance warning, intersection coordination, etc. Usually direct one-hop broadcast is demanded due to the stringent delay requirements in high mobility scenario. Three reliability metrics, which were the packet reception rate（PRR）, PRR with distance d from the sender（PRR（d））and the node packet delivery probability（PDP）, were evaluated for one-hop broadcast at an intersection in 2-D VANET analytically. Expressions of these metrics were derived with consideration of the hidden terminal problem and collisions caused by concurrent transmissions. The impact of carrier sensing and interference ranges, the packet size, the back-off window size and the density of nodes on the reliability were investigated and discussed. Finally, some important observations to the broadcast at an intersection in 2-D VANET were provided, such as the PRR, PRR（d）and PDP were getting worse with the traffic density increase.